Nas margens, currículos com gêneros e sexualidades: uma leitura a partir dos anos finais do ensino fundamental em escolas estaduais de Campina Grande - PB - Silva, Adjefferson Vieira Alves da (2021)
This doctoral research, developed in the Graduate Program in Education at the Federal University of Paraíba, inserted in the line of research: Cultural Studies of Education, has as its object "Curriculum with Gender and Sexualities" in the final years of Elementary School. Experience in the final years of Elementary School has shown that gender and sexuality are approached in a timely manner by teachers politically and ethically involved with these themes. In the same direction, a survey carried out with research repositories showed that there are few studies on the themes in this stage of teaching of Basic Education, while no study was found in / about the territory of Paraíba. This time, anchoring in Cultural Studies of Education, in its post-critical perspective, in Curriculum Studies, Gender Studies and Sexuality Studies, the present research questions: if and how gender relations and sexualities are addressed in the curricula of Elementary School in their final years in Integral Citizen Schools (ECI-ESCOLAS CIDADÃS INTEGRAIS) belonging to the 3rd Regional Education Management (3ª GRE-GERENCIA REGIONAL DE ENSINO) and located in Campina Grande - Paraíba? Based on this question, the main objective is to analyze, from documental sources and from the perspective of teachers, the approach to gender and sexuality issues in the curricula of Elementary School, final years, in Intergral Citizen Schools (ECI- ESCOLAS CIDADÃS INTEGRAIS) of Campina Grande -PB. We start with a double clue: The first is that the curriculum policy documents - at the national and state level - allow for the approach/problematization present in the curriculum documents regarding issues of gender and sexualities, even if through alternative pathways / not explicit. The second clue assumes that, taking the possibilities of approach/problematization present in the curricular documents regarding gender and sexuality issues, it is expected that teachers materialize/address/problematize such issues, even if tangentially. For all that, this research is qualitative in terms of objectives and procedures and applied in terms of results. In the production of empirical material, documental research strategies are used to access and safeguard curriculum policy documents, as well as documents from school pedagogical routines. An online questionnaire is also produced to select educators familiar with an approach to the theme of gender and sexuality, active in the selected schools; and, finally, online semi-structured episodic interviews are carried out with teachers. The empirical material was analyzed from the perspective of Cultural Analysis. At the end of the analyses, it was concluded that the texts of the curriculum policy, in its various scopes, and the teaching perspective make it possible to sustain that the approach/problematization of gender and sexuality issues is based on Brazilian educational legislation and, associated with these legal documents , there is a willingness of teachers to address the issue of diversity (of genders and sexual orientations), despite the fear that the environment of political, ideological and moral surveillance installed in the country for years, with special emphasis on Education.